2000
DOI: 10.1177/0265407500176008
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Desired Characteristics of Short-Term and Long-Term Relationship Partners

Abstract: This investigation compared women's and men's desired characteristics in partners for typical short-term ('dating someone more than once' without an expectation of a short- or long-term relationship) and long-term ('dating someone for a long time' with the possibility, but not certainty, of marriage) relationships. Results indicated that (a) both women and men are more selective when selecting a long-term rather than a short-term relationship partner, and (b) women and men differ in their desired characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 8 publications
7
80
0
Order By: Relevance
“…This given is in line with the literature (Altafim et al, 2009;Buss, 1989Buss, , 2006Buss & Schmitt, 1993;Castro, 2009;Cruz, 2009;Carneiro, 1997;Greengross & Miller, 2008;Lippa, 2007;Stewart et al, 2000), as is the case of the great importance attached to the first two macro-categories in long-term relationships, and to the last in short-term relationships, as predicted in the first hypothesis Campos, 2005;Castro, 2009;DeWaal & Maner;Lucas et al, 2011;Schmitt, 2005;Stewart et al, 2000).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This given is in line with the literature (Altafim et al, 2009;Buss, 1989Buss, , 2006Buss & Schmitt, 1993;Castro, 2009;Cruz, 2009;Carneiro, 1997;Greengross & Miller, 2008;Lippa, 2007;Stewart et al, 2000), as is the case of the great importance attached to the first two macro-categories in long-term relationships, and to the last in short-term relationships, as predicted in the first hypothesis Campos, 2005;Castro, 2009;DeWaal & Maner;Lucas et al, 2011;Schmitt, 2005;Stewart et al, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…Due to the difference in parental investment between genders, men and women display significant differences, like the high valuation of good provision of resources and attachment formation among women, and the high appraisal of physical attributes among men (Altafim, Lauandos, & Caramaschi, 2009;Buss, 1989Buss, , 1995Buss, , 2006Buss & Schmitt, 1993;Campos, 2005;Carneiro, 1997;Castro, 2009;Covolan, 2005;Cruz, 2009;Fiore, 2010;Furnham, 2009;Greengross & Miller, 2008, Hattori, 2009Lippa, 2007;Sadala, 2005;Stewart, Stinnett, & Rosenfelt, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, because women's reproductive value declines steeply over the life course, men will prefer cues indicating a woman's physical ability to reproduce-such as youth and beauty-more than will women (Symons, 1979). There is to date a great deal of evidence to support these predictions, including numerous studies documenting sex differences in preferences for these traits across many populations and using a variety of methods (Buss, 1989a(Buss, , 1989bBuss & Barnes, 1986;Buunk, Dijkstra, Fetchenhauer, & Kenrick, 2002;Hatfield & Sprecher, 1995;Khallad, 2005;Li, Bailey, Kenrick, & Linsenmeier, 2002;Lippa, 2007;Shackelford, Schmitt, & Buss, 2005;Stewart, Stinnett, & Rosenfeld, 2000;Zeh & Smith, 1985). In fact, so often has it been reported that men consider physical attractiveness more importantly in a long-term partner than do women and that women consider access to resources more importantly than do men that these sex differences are beginning to be treated as truisms (e.g., Greitemeyer, 2007;Koyama, McGain, & Hill, 2004;Wiederman & Allgeier, 1994).…”
Section: Evidence Supports Predictions Derived From Parental Investmementioning
confidence: 99%
“…For instance, studies have examined preferences for traits like ''ambitiousness'' (Howard, Blumstein, & Schwartz, 1987;Hoyt & Hudson, 1981;Hudson & Henze, 1969;McGinnis, 1958), ''good earning capacity'' (Buss, 1989;Stewart, Stinnett, & Rosenfeld, 2000), ''good financial prospects'' (Buss, 1989), ''educated'' (Greitmeyer, 2005;Kenrick, Sadalla, Groth, & Trost, 1990;Lance, 1998), having high ''social status,'' ''social level, '' or ''prestige'' (Feingold, 1992;Townsend & Levy, 1990;Townsend & Wasserman, 1998) -traits thought to be related to one's ability to generate income. Consistently, women value mates with these traits more than men do (Townsend, 1993;Townsend & Roberts, 1993).…”
Section: Preferences For Resourcesmentioning
confidence: 99%